PENGARUH PENGGUNAAN MEDIA FOCUSKY TERHADAP HASIL BELAJAR SISWA PADA SUBMATERI PEMISAHAN CAMPURAN - Elsye Apriliantika; Eny Enawati; Masriani Masriani; Husna Amalya Melati; Maria Ulfah (Jurnal Ilmiah Ar-Razi, 2021)
This research is based on the problems experienced in schools, namely the problems of the learning media used. This research uses a quasi-experimental form, namely a quasi-experimental design research and the design used is a non-equivalent control group design. This study was to determine the comparison of learning outcomes between classes using Focusky media and classes using PowerPoint media at SMP Negeri 21 Pontianak in Mixed Separation SubMaterial and to know the impact of using Focusky Media on the learning outcomes of seventh grade students at SMP Negeri 21 Pontianak. The research sample was 57 students consisting of 28 students in class VII B, namely the control class and 29 students in class D, the experimental class. Based on the results obtained, the value of the experimental class is greater than the control class. For statistical analysis, the pretest data used a t-test and showed that there were still differences in the pretest results in the two classes with a sig. (2- tailed) value of 0.001 so that the N-Gain test was carried out, obtained a value of 0.48 and was in the medium category. The effect size value shows a value of 46, 78, the results are categorized as moderate so that Focusky media-assisted learning is efficient in increasing student learning outcomes.